Case Report: Three-fraction lattice radiotherapy followed by VMAT concurrent chemoradiotherapy in locally advanced non–small cell lung cancer - Zhou, Chunyang; Liu, Hong; Yan, Chao; Yang, Tao; Yang, Aijie; Liu, Xiangyong; Liu, Xiaoli; Wang, Zijian (Frontiers in Oncology, 2026)
BackgroundIn unresectable stage III non–small cell lung cancer (NSCLC) with bulky primary tumors and extensive nodal irradiation volumes, dose escalation during concurrent chemoradiotherapy (cCRT) is often limited by the tolerance of organs at risk (OARs). Lattice radiotherapy (LRT), a form of spatially fractionated radiotherapy (SFRT), generates a characteristic intratumoral peak–valley dose distribution, which may enable focal dose intensification without increasing the dose to surrounding normal tissues.Case descriptionA 65-year-old man with unresectable stage IIIC (cT4N3M0) poorly differentiated squamous cell carcinoma of the right upper lobe first underwent 3 fractions of LRT. He then received volumetric modulated arc therapy (VMAT) delivered concurrently with platinum-doublet chemotherapy. During treatment, cone-beam CT (CBCT) demonstrated marked tumor regression; a second CT simulation was performed and target volumes were recontoured, reducing the primary gross tumor volume (GTVp). The patient completed the remaining 14 fractions using the new plan. Treatment was well tolerated, with only grade 1 sore throat and reversible anemia, both improving with supportive care. One month after completion, chest CT showed substantial tumor shrinkage consistent with a partial response (PR) per RECIST v1.1. Approximately 1.5 months post-treatment, radiation-induced pneumonitis occurred and improved with anti-infective/supportive management. The Eastern Cooperative Oncology Group (ECOG) performance status remained 0–1 during follow-up.ConclusionsThis case suggests that, in unresectable stage III pulmonary squamous cell carcinoma, a combined strategy of limited-fraction LRT plus VMAT with concurrent chemotherapy, together with on-treatment adaptive replanning, can achieve favorable short-term efficacy and acceptable toxicity while maintaining OAR doses within constraints. This approach provides a practical reference for individualized radiotherapy with complex target volumes.